Land Resource Management: Geoinformation Support of Internal Controlling - NEPOMNYASHCHIKH, Ivan Fedorovich; LAZAREVA, Oksana Sergeevna; ARTEMYEV, Alexey Anatolyevich (Journal of Environmental Management and Tourism; Vol 10 No 5 (2019): JEMT Volume X Issue 5(37) Fall 2019, 2019)
The trend towards globalization of the world economy is currently increasing. Therefore, corporate entities seek to expand their economic power and influence. It spurs them to constantly look for ways to improve the efficiency of their activities, both in the domestic and foreign markets. These circumstances force corporate structures to accelerate the pace of their development. In this regard, they introduce innovations, reduce costs, use available resources more efficiently, as well as optimize the selection of missing ones, including land resources. Comprehensive and up-to-date information on the existing assets and liabilities contained in the geographic information system(s) and assessment of the efficiency of their use can help companies expand their economic possibilities. The creation of relevant databases and their interpretation become possible with the use of modern geoinformation technologies for creating and processing localized geospatial information about land plots and everything closely related to them. The purpose of the study is to identify the possibility of using and assessing the total data on land resources and everything related to them. These data are stored in the relevant geoinformation system(s) to increase the efficiency of controlling in the framework of the corporate management system. The main scientific results and conclusions obtained by the authors in the course of this study are as follows: The possibility of improving the efficiency of controlling through the use of geoinformation support and geoinformation systems as a source of receiving, processing, interpreting, and visualizing geospatial data on corporate and other land and property resources has been proved. The methodology for assessing the efficiency of land use based on the author’s cube model and the suggested rating criteria has been proposed.